Boundary between discourse analysis and historical semantic of enunciation: theoretical approaches - Steigenberger, Fabiana Fernanda; Machado, Julio Cesar; da Silva, Soeli Schreiber (Revista de estudos da linguagem, 2011)
This article brings to scientific inquiry a statement about informal space: "Does it mean that Discourse Analysis (DA) and Historical Semantics of Enunciation (HSE) are the same thing?" Much more than just a naive and unsuspecting assertion, we can see that researchers stymied by this unknown that leads to chaotic research practice, in which the misuse and inverted theoretical apparatus of one theory inside the other, ends up producing miscellaneous scientific effects. We reveal an involuntary practice of "cheating with science" by unifying two theoretical fields, making this article therefore worthy of attention. We selected as the object some devices of analysis present in DA and HSE for the purpose of drawing a parallel between them and identifying possible nearness and distance. Adapted from the source document